Recent topics on the regulatory mechanism of ecdysteroidogenesis by the prothoracic glands in insects. - TANAKA, Yoshiaki (Frontiers in Endocrinology, 2011)
Molting and metamorphosis are strictly regulated by steroid hormones known as ecdysteroids. It is now widely recognized that ecdysteroid biosynthesis (ecdysteroidogenesis) in the prothoracic gland (PG) is regulated by the tropic factor prothoracicotropic hormone (PTTH). However, the importance of PTTH in the induction of molting and metamorphosis remains unclear, and other mechanisms are thought to be involved in the regulation of ecdysteroidogenesis by the PG. Recently, new regulatory mechanisms, prothoracicostatic factors, and neural regulation have been explored using the silkworm, Bombyx mori, and two circulating prothoracicostatic factors, prothoracicostatic peptide (PTSP) and Bommo-myosuppressin (BMS), have been identified. Whereas PTTH and BMS are secreted from the brain, PTSP is secreted from the peripheral neurosecretory system—the epiproctodeal gland—during the molting stage. The molecular basis of neural regulation of ecdysteroidogenesis has been revealed for the first time in B. mori. The innervating neurons supply both Bommo-FMRF related peptide (BRFa) and orcokinin to maintain low levels of ecdysteroids during the feeding stage. These complex regulatory mechanisms—involving tropic and static factors, peripheral neurosecretory cells as well as the central neuroendocrine system, and neural regulation in addition to circulating factors collaborate to regulate ecdysteroidogenesis. Thus, together they create the finely-tuned fluctuations in ecdysteroid titers needed in the hemolymph during insect development.